Synergistic effect of Polymer-Augmented low salinity flooding for oil recovery efficiency in Illite-Sand porous media - Abdullahi, M.B. (Elsevier B.V., 2022)
Low salinity water (LSW) flooding is a novel and emerging technique for oil recovery and has received significant attention recently by petroleum industries as an efficient, economical, and environmentally friendly method compared to other secondary and tertiary oil recovery methods. Although LSW flooding has been proven to be a promising technique, its conjunction with the traditional polymer flooding process (called low salinity polymer, LSP flooding) to control flood front mobility of LSW could be a game-changer. A very few studies have investigated the effectiveness of LSP flooding in terms of oil recovery efficiency. But the effect of clay minerals such as illite present in the hydrocarbon reservoir has remained to be investigated. Herein, this work reports the injection of the partially hydrolyzed polyacrylamide (HPAM) polymer augmented LSW flooding into an oil-saturated sandpack consisting of sand (98) and illite (2). HPAM characterization and effect of polymer concentration (1000â5000 ppm), salinity (0â60000 ppm), and temperature (26â â 70â) on the rheological behaviour of the HPAM solution has been investigated. The possible mechanisms have also been discussed to understand the interaction between illite and LSP slug in the sandpack. The sandpack flooding experiments reveal that the LSP flooding recovered more additional oil (42.7) than high salinity polymer (HSP) flooding (35.4), with an ultimate oil recovery of 67.7 and 60.4 , respectively. However, in the absence of polymer, oil recovery was limited to only 25 of the original oil in place (OOIP). The findings of this study can help to understand the synergistic effect of LSW and variety of polymeric solutions on oil recovery in the presence of different clay minerals. Â© 2022 Elsevier B.V.